Effectiveness of Center Led Action Network (CLAN) purchasing approach: a case study on O&M materials purchasing by Gazipur PBS - Firozi, Md. Monowarul Islam (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.